Isolation and cytotoxic activity study of phytochemicals from Calophyllum canum - Bakhtiar, M. Taher; Arief Ichwan, Solachuddin Jauhari; Alkhamaiseh, Suhaib Ibrahim; Suilam Ngoto, Shahida ([s.n.], 2010)
Calophyllum canum is a large tree which grows in South East Asia and which is popular for its timber. This plant belongs to the family Guttiferae; a family that boasts species which are rich in bioactive phytochemicals. The present study was conducted to screen for the antiproliferation activity of three crude extracts from the stem bark of C. canum. The activity of an isolated compound against canacer cells was also reported. The three extracts; n-hexane, ethyl acetate and methanol extracts, were screened on human cervical (C33A), colon (CACO2), lung (A549), esophageal (TE1), breast (MCF7) cancer cell lines along with normal human dermal fibroblast cells (NHDF) and leukemia cancer cells (K562) . The MTT assay and direct counting by tryphan blue were used to assess the antiproliferation activity of the extracts on the cell lines. The study revealed that the n-hexane extract had the strongest antiproliferation activity, followed by the methanol extract. n-hexane strongly inhibited the growth of TE1 and MCF7 cell lines. IC50 for n-hexane and methanol extract activity on the A549 cell line was found to be 27.96 µg/mL and 78.9 µg/mL respectively. The IC50 for the n-hexane extract activity on the NHDF cell line was found to be 70.59 µg/mL. The ethyl acetate extract showed no activity against any of the cell lines. An isolated compound labeled as CE2 was found to be active against K562 cells with IC50 value of 11µg/mL.